Smoking Behavior among Adolescents: A Case Study in Daksa Lok Bahu Housing Complex, Samarinda - Safitrie, Annisa; Chifdillah, Nino Adib; Bernadetha, Bernadetha (Jurnal Penelitian dan Kajian Ilmiah Kesehatan Politeknik Medica Farma Husada Mataram, 2025)
Smoking behavior among adolescents remains a growing public health concern. Adolescents represent a vulnerable group, easily influenced by their social environment, peer pressure, and limited self-control. This study aims to explore smoking behavior among adolescents in the Daksa Lok Bahu Samarinda Housing Complex using the Theory of Reasoned Action (TRA) and Theory of Planned Behavior (TPB) frameworks, focusing on three key components: attitudes, subjective norms, and perceived behavioral control. A qualitative case study with a phenomenological approach was employed. Data were collected through in-depth interviews with seven informants, including five adolescent smokers, one shop owner, and one peer, selected through purposive sampling. The findings reveal that although adolescents are aware of the health risks, smoking is perceived as a source of relaxation, confidence, and social acceptance. Peer influence and smoking behavior within the family reinforce permissive subjective norms, while perceived control to quit smoking remains low due to limited support and weak self-regulation. Smoking activities commonly occur outside school settings, such as at food stalls, friends’ houses, or cafés. In conclusion, adolescent smoking behavior is shaped by the interaction of favorable attitudes, permissive social norms, and low perceived behavioral control. Preventive strategies should therefore integrate health education with family and peer-based interventions to reduce smoking prevalence among adolescents